2022
DOI: 10.1002/fsn3.2849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of roasting on the phenolic and volatile compounds in coffee beans

Abstract: Phenolic compounds present in coffee beans could generate flavor and bring benefits to health. This study aimed to evaluate the impacts of commercial roasting levels (light, medium, and dark) on phenolic content and antioxidant potential of Arabica coffee beans (Coffea arabica) comprehensively via antioxidant assays. The phenolic compounds in roasted samples were characterized via liquid chromatography–electrospray ionization quadrupole time‐of‐flight mass spectrometry (LC‐ESI‐QTOF‐MS/MS). Furthermore, the cof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 115 publications
3
32
0
Order By: Relevance
“…The Maillard reaction was the main pathway for producing flavor during the roasting process, and amino acids and sugars are the most important precursors to the Maillard reaction [ 24 ]. However, different amino acids and sugars as precursors could generate different coffee flavors.…”
Section: Resultsmentioning
confidence: 99%
“…The Maillard reaction was the main pathway for producing flavor during the roasting process, and amino acids and sugars are the most important precursors to the Maillard reaction [ 24 ]. However, different amino acids and sugars as precursors could generate different coffee flavors.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorogenic acids were classified into a class of esters derived from hydroxycinnamic acids (phenols mainly include caffeic, ferulic, and p‐coumaric acids) and quininic acids with specific phenols. These compounds may affect the final cup quality of coffee; therefore, it is important to understand the phenolic acid content obtain in coffee (Doncea, 2010; Wu et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In roasted beans, the total phenolic content had generally lower values than in unroasted green beans. Studies indicated that as the roasting degree was higher, the total phenolic content will be lower as the phenolic compounds was highly thermal instable which compounds can be easily decomposed in high temperature of roasting (Wu et al, 2022). However, coffee beans with starter culture inoculated improved the total phenolic content, as reported by (Bressani et al, 2021)'s study.…”
Section: Resultsmentioning
confidence: 99%
“…Te main phenolic acid in cofee is chlorogenic acid (CGA) [91]. CGA can provide favor of bitter, sour, and astringent in cofee brewing, especially cafeoylquinic and feruloylquinic acids [92]. Feruloylquinic and cafeoylquinic acid also furnishes excellent functions of high antioxidant, antibacterial, antiviral, and chemopreventive capacity, which improve the nutritional value of brewing cofee [93].…”
Section: Accuracy and Sensitivitymentioning
confidence: 99%